Peningkatan Kualitas Mie Basah Dengan Penambahan Tepung Talas Pratama (Colocasia esculeta L. schott var. Pratama) dan Tepung Rumput Laut (Eucheuma cottonii) - Yusman Taufik; Yudi Garnida; Thomas Gozali; Yusep Ikrawan; Diva Apresya (Politeknik Negeri Lampung., 2023)
The purpose of this study was to determine the effect of taro flour and seaweed flour on the quality of the wet noodles produced. Wet noodle research was carried out in two stages, namely preliminary research and main research. Preliminary research includes analysis of oxalate content of taro tubers and taro flour, as well as analysis of raw materials including analysis of water content, analysis of carbohydrates and protein content. Then the main research was carried out, namely to determine the effect of the comparison of pratama taro flour and seaweed flour on wet noodles where chemical and organoleptic analyzes were carried out. Chemical testing includes analysis of water content, analysis of carbohydrates and analysis of protein. Testing the organoleptic response in the form of aroma, taste, color and texture. The method used was a randomized block design (RBD) which consisted of 1 factor, namely the T factor (comparison of taro pratama flour and seaweed) which consisted of 5 levels, namely t1 (3:1), t2 (2:1), t3 (1 :1), t4 (1:2) and t5 (1:3). The results of the comparative study of the addition of pratama taro flour and seaweed flour had an effect on water content, carbohydrate content, protein content, aroma, color and texture, but had no effect on taste. Keywords: Taro Tubers, Seaweed, Wet Noodles, Randomized Block Design (RBD)